2021
DOI: 10.1038/s41467-021-22533-1
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-site nucleation for growing twisted bilayer graphene with a wide range of twist angles

Abstract: Twisted bilayer graphene (tBLG) has recently attracted growing interest due to its unique twist-angle-dependent electronic properties. The preparation of high-quality large-area bilayer graphene with rich rotation angles would be important for the investigation of angle-dependent physics and applications, which, however, is still challenging. Here, we demonstrate a chemical vapor deposition (CVD) approach for growing high-quality tBLG using a hetero-site nucleation strategy, which enables the nucleation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 53 publications
3
89
0
Order By: Relevance
“…To achieve this, the fabrication of MATBG devices should avoid high temperature, the formation of bubble between two graphene layers, and the additional strains. Note that, CVD approach, which is suitable for the production of graphene films on a large scale, is also capable of growing twist bilayer graphene 645 . However, it remains difficult to produce twist bilayer graphene with fine control over twist angle, especially the magic angle near zero, owing to the overwhelming stability of AB-stack bilayer graphene.…”
Section: Magic-angle 2d Superlatticesmentioning
confidence: 99%
“…To achieve this, the fabrication of MATBG devices should avoid high temperature, the formation of bubble between two graphene layers, and the additional strains. Note that, CVD approach, which is suitable for the production of graphene films on a large scale, is also capable of growing twist bilayer graphene 645 . However, it remains difficult to produce twist bilayer graphene with fine control over twist angle, especially the magic angle near zero, owing to the overwhelming stability of AB-stack bilayer graphene.…”
Section: Magic-angle 2d Superlatticesmentioning
confidence: 99%
“…We can also observe sharp edges of the BLG domains through optical microscopic images. 32 The AB-stacked BLG domains account for ∼75%, and the rest are mostly 30° twisted angles ( Figures S5 and S6 ). It had been reported that the orientation of the second graphene layer can be affected by the environment of graphene growth, such as the variation in gas flow and distinct interface energy between the adlayer graphene and graphene/Cu steps.…”
Section: Resultsmentioning
confidence: 99%
“…However, the progress in this direction is not promising as most of the structures obtained either have the R-type (0°) stacking orientations or the H-type (60°) stacking orientations, as they are energetically favorable in the CVD growth process ( Liu et al., 2014 ). Few strategies, including heterosite nucleation ( Sun et al., 2021 ), temperature triggered misalignment ( Omambac et al., 2019 ), metal-semiconductor stacking ( Li et al., 2020a ), epitaxial intercalation of graphene under hydrogen-terminated hBN template ( Wang et al., 2021a ), are recently reported that showed the potential of CVD to generate moiré phase. Still, stringent control on interlayer twist angle is challenging and needs to be encountered soon.…”
Section: Excitons In Tmds Based Heterostructuresmentioning
confidence: 99%